Synergistic Degradation of Pyrethroids by the Quorum Sensing-Regulated Carboxylesterase of Bacillus subtilis BSF01 - Xiao, Ying; Lu, Qiqi; Yi, Xin; Zhong, Guohua; Liu, Jie (Frontiers in Bioengineering and Biotechnology, 2020)
The well-studied quorum sensing (QS) mechanism has established a complex knowledge system of how microorganisms behave collectively in natural ecosystems, which contributes to bridging the gap between the ecological functions of microbial communities and the molecular mechanisms of cell-to-cell communication. In particular, the ability of agrochemical degradation has been one most attractive potential of functional bacteria, but the interaction and mutual effects of intracellular degradation and intraspecific behavior remained unclear. In this study, we establish a connection between QS regulation and biodegradation by harnessing the previously isolated Bacillus subtilis BSF01 as a template which degrades various pyrethroids. First, we characterize the genetic and transcriptional basis of comA-involved QS system in B. subtilis BSF01 since the ComQXPA circuit coordinates group behaviors in B. subtilis isolates. Second, the genetic and transcriptional details of pyrethroid-degrading carboxylesterase CesB are defined, and its catalytic capacity is evaluated under different conditions. More importantly, we adopt DNA pull-down and yeast one-hybrid techniques to reveal that the enzymatic degradation of pyrethroids is initiated through QS signal regulator ComA binding to carboxylesterase gene cesB, highlighting the synergistic effect of QS regulation and pyrethroid degradation in B. subtilis BSF01. Taken together, the elucidated mechanism provides novel details on the intercellular response of functional bacteria against xenobiotic exposure, which opens up possibilities to facilitate the in-situ contaminant bioremediation via combining the QS-mediated strategies.